Influence of Accelerometer Calibration Approach on Moderate–Vigorous Physical Activity Estimates for Adults—Corrigendum. Issue 9 (September 2021) - Matthews, Charles E.; Keadle, Sarah K.; Berrigan, David; Lyden, Kate; Troiano, Richard P.
Abstract : Supplemental digital content is available in the text.